Family control and the implied cost of equity: Evidence before and after the Asian financial crisis - Boubakri, Narjess; Guedhami, Omrane; Mishra, Dev (Journal of International Business Studies, 2010)
Recent research emphasizes that corporate governance becomes critical during economic crises, when the incentives for expropriation of minority shareholders increase. Using the high-profile Asian financial crisis of 1997–1998 and a sample of 566 firms from eight East Asian countries over 1996–1999, we examine the link between family control and agency costs evident in the cost of equity financing for firms. We find that, before the crisis, family control is unrelated to firms' equity financing costs, whereas, following the crisis, family control is related to a higher cost of equity. This suggests that the crisis made investors aware of the potential entrenchment of controlling families, prompting them to require a higher-equity premium from family firms. Our results are robust to various models of the cost of equity capital, additional firm- and country-level governance traits, and additional alternative explanations, including the presence of other types of large shareholders and potential survivorship bias. Our study contributes to our understanding of the corporate governance of family-controlled firms, especially during economic crises.